Magnetic and magnetothermal properties, and the magnetic phase diagram of single-crystal holmium along the easy magnetization direction. (19th March 2015) - Zverev, V I; Tishin, A M; Min, Zou; Mudryk, Ya; Jr, K A Gschneidner; Pecharsky, V K
Abstract: The magnetic and magnetothermal properties of holmium single crystal have been investigated from 4.2 to 300 K in magnetic fields up to 100 kOe using magnetization and heat capacity data measured along the easy magnetization direction, which is the crystallographic b -axis, i.e. direction. The magnetic phase diagram of Ho has been refined by examining data measured using a high purity single crystal.